Pembinaan Kantin Sehat pada SDN 01 Ladang Laweh, Kecamatan Banuhampu, Kabupaten Agam - Putri Nilam Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The food security system is an effort to control food, people, places, equipment factors and free from substances that can cause health problems and even food poisoning. Primary school is the second place after the household, a potential place for poisoning, mostly caused by snacks due to the poor quality of street food and does not meet requirements such as containing chemicals, poor sanitation conditions, and biological contamination. To obtain safe and nutritious food in schools, the government requires that each educational unit have facilities and infrastructure, including a school canteen that is healthy and ecologically comfortable. SDN 01 Ladang Laweh already has a good policy regarding school canteens. The food provided for students is free from preservatives and is dominated by traditional foods. However, the food provided still does not meet the requirements for balanced nutrition, and schools do not have adequate facilities to create a healthy canteen for school residents. Therefore, this service is carried out to create a proper healthy canteen for students and school residents. This activity was done by discussions with the principal and canteen managers regarding implementing a healthy canteen. Then providing counseling, pre, and post-test before and after counseling, analyzing the comparison of student knowledge before and after being given counseling; holding quizzes and questions and answers session about healthy canteens and healthy food. After counseling, there was an increase in students' understanding of the canteen and healthy food. Schools can use healthy canteen facilities to improve sanitation and ensure food safety of the canteen.